2012
DOI: 10.1111/pcmr.12005
|View full text |Cite
|
Sign up to set email alerts
|

Hic‐5 affects proliferation, migration and invasion of B16 murine melanoma cells

Abstract: Summary Hic‐5 is a shuttling protein between the cell membrane and the nucleus which functions as a focal adhesion adaptor protein and a nuclear receptor coactivator. Although several studies have shown its involvement in other types of cancer, the role of Hic‐5 in melanoma is unknown. Herein, we show for the first time that Hic‐5 is expressed in B16‐F1 murine melanoma cells. To determine its function in melanoma cells, we used shRNA‐mediated RNA interference and established stable clones with down‐regulated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Furthermore, ectopic expression of Hic-5 is sufficient to promote normal mammary cells to undergo EMT [ 27 ]. In addition, the melanoma cell depleted of Hic-5 exhibit decreased cell motility and metastatic activity in vivo [ 28 ]. One recent report demonstrated the upregulation of Hic-5 in HCCs overexpressing proline-rich tyrosine kinase 2 (Pyk2) [ 29 ], which is known to be involved in HCC metastasis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ectopic expression of Hic-5 is sufficient to promote normal mammary cells to undergo EMT [ 27 ]. In addition, the melanoma cell depleted of Hic-5 exhibit decreased cell motility and metastatic activity in vivo [ 28 ]. One recent report demonstrated the upregulation of Hic-5 in HCCs overexpressing proline-rich tyrosine kinase 2 (Pyk2) [ 29 ], which is known to be involved in HCC metastasis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as previously described (33). Antibodies used were: mouse monoclonal anti-ATP synthase beta IgG (1:10,000; 612518, BD Biosciences), rabbit polyclonal anti-PGC-1 IgG (1:200; sc-13067, Santa Cruz Biotechnology), rabbit polyclonal anti-cleaved caspase-3 p11 IgG (1:200; sc-22171-R, Santa Cruz Biotechnology), rabbit polyclonal anti-cleaved caspase-6 (Asp162) IgG (1:1,000; #9761, Cell Signaling Technology), and anti-b-actin (1:20,000; A5441, Sigma-Aldrich).…”
Section: Western Blottingmentioning
confidence: 99%
“…In the cytosol, it acts as a scaffold at focal adhesions and controls important cellular processes such as proliferation, invasion, and apoptosis (25)(26)(27). In the nucleus, we and others have shown that it functions as a nuclear receptor coactivator in transient reporter gene assays (24,28).…”
Section: Significancementioning
confidence: 99%